PENGARUH HARGA SAHAM, VOLUME PERDAGANGAN DAN SUKU BUNGA TERHADAP LIKUIDITAS SAHAM PADA PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2015)
This study aimed to determine the effect of stock price, trade volume and rate of interest on the stock liquidity. The data in this study using secondary data and the sampling technique in this study using purposive sampling. The criterion are food and beverage company that listing on BEI in 2010-2012, have profit during 2010-2012 and have financial report on rupiah. There are fourteen companies that meet the criterion. Analysis tool used is multiple linear regression. The results showed that stock price, trade volume and rate of interest have simultaneously effect on the stock liquidity with significance level of 0.000 < 0.05. Beside that, the results showed that only trade volume has partially effect on the stock liquidity with significance level of 0.000 < 0.05. Stock price and rate of interest have no partially effect on the stock liquidity with significance level of 0.086 and 0.781 > 0.05.